STRATEGI PENGEMBANGAN METODE PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DALAM UPAYA MENANAMKAN NILAI-NILAI MORAL DI SEKOLAH MENENGAH PERTAMA PELEPAT ILIR - Sulastri Sulastri (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2018)
The development of learning in the classroom plays an important role in efforts to develop character, moral values, and student learning outcomes. Development efforts must be carried out in a continuous manner, paying attention to the needs of students in learning. This paper aims to describe the learning strategy of citizenship education (PKN) for junior high school students to instill moral values in education, which will later be used as a further step in conducting classroom action research in school, especially in junior high school.